Conductive particle and preparation method and application thereof

By using silicone microspheres as cores and combining metal electroless plating, conductive particles with core-shell structures are prepared, which solves the problems of poor uniformity of existing conductive particles and poor high-temperature resistance, and realizes high-temperature resistance, cracking resistance and hardness of conductive particles, which improves the reliability of electronic packaging.

CN119763901APending Publication Date: 2025-04-04SHENZHEN INST OF ADVANCED ELECTRONICS MATERIALS +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510208712.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The pure metal conductive particles used in existing anisotropic conductive adhesives have poor uniformity and poor high temperature resistance, which affects the electrical interconnection performance and reliability.

Method used

By using silicone microspheres as the core and combining with the strong reduction properties of the metal electroless plating solution, conductive particles with core-shell structures were prepared by electroless plating to achieve the regulation of particle size uniformity and hardness.

Benefits of technology

The prepared conductive particles have the advantages of high temperature resistance, good crush resistance, and adjustable hardness, which improves the reliability of electronic packaging and is suitable for narrow pitch and high density electrical interconnection fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119763901A_ABST
    Figure CN119763901A_ABST
Patent Text Reader

Abstract

The invention provides a conductive particle and a preparation method and application thereof, the conductive particle has a core-shell structure, the core layer of the conductive particle is an organosilicon microsphere, and the shell layer is a metal coating. The conductive particle obtained by using the organic silicon microspheres as the inner core has the advantages of uniform and controllable particle size, high temperature resistance, good crushing resistance and the like; the modulus of the conductive particles can be adjusted by regulating the thickness of the metal coating, and the process is mild, simple and convenient; the conductive particle provided by the invention has a wide application prospect in a high temperature scene and a scene with a relatively high requirement on particle compression resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of conductive functional materials, and relates to conductive particles and a preparation method and application thereof, and in particular to conductive particles with adjustable compression modulus and a preparation method and application thereof. Background Art

[0002] Anisotropic conductive adhesive (ACA) is a special conductive functional material that has the characteristics of being conductive in the vertical direction and insulating in the horizontal direction after hot pressing bonding. Anisotropic conductive adhesive is mainly composed of an insulating resin matrix and conductive particles dispersed therein. The uniformity, heat resistance, chemical stability and hardness of the conductive particles have an important influence on the conductive performance and reliability of anisotropic conductive adhesive.

[0003] The pure metal conductive particles used in traditional anisotropic conductive adhesives, such as silver, nickel and gold, have poor particle uniformity, which can easily cause poor contact of some conductive particles, affecting the electrical interconnection performance of the anisotropic conductive adhesive; and the cores of the core-shell structure conductive microspheres on the market, such as polymethyl methacrylate, polystyrene microspheres and polydivinylbenzene microspheres, have poor high temperature resistance. The thermal deformation temperature of polymethyl methacrylate is only 100°C, and the melting point is only 130-140°C. When the packaged device is used at a higher temperature, the polymer core and the metal shell are prone to breakage and separation. In addition, the hardness of the above-mentioned microspheres is low, and it is difficult to pierce the oxide layer of the chip bump or substrate pad during the hot pressing bonding process, affecting the interconnection reliability of the anisotropic conductive adhesive.

[0004] Therefore, developing a conductive particle that is resistant to high temperatures, has good chemical stability, adjustable hardness, and uniform particle size is of great significance to improving the reliability of electronic packaging. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a conductive particle and a preparation method and application thereof, and specifically to provide a conductive particle with adjustable compression modulus and a preparation method and application thereof. The present invention utilizes the organic-inorganic hybrid structure of organosilicon microspheres and the strong reducing property of the reducing agent in the metal chemical plating solution to prepare functional conductive particles with core-shell structure having different compressive elastic moduli and uniform particle size through the principle of chemical plating, which has important application prospects in the field of narrow pitch and high-density electrical interconnection.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a conductive particle having a core-shell structure, wherein the core layer of the conductive particle is an organosilicon microsphere and the shell layer is a metal coating.

[0008] The present invention uses organic silicon microspheres as the core of the conductive particles, so that the conductive particles have high temperature resistance and crushing resistance, and the hardness of the conductive particles is adjustable and the particle uniformity is good.

[0009] Preferably, the particle size of the silicone microspheres is 1 to 200 μm, for example, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, etc., preferably 1 to 10 μm.

[0010] Preferably, the raw materials for preparing the organosilicon microspheres include: methylsilane, vinylsilane and ammonia solution.

[0011] Preferably, the methylsilane includes any one of methyltrimethoxysilane, methyltriethoxysilane, polydimethylsiloxane, mercaptopropyltrimethoxysilane, hexamethyldisiloxane, cyclomethylsiloxane, polymethylphenylsiloxane, or a combination of at least two thereof.

[0012] Preferably, the vinyl silane is selected from any one or a combination of at least two of vinyl trimethoxy silane, vinyl triethoxy silane, tetramethyl divinyl disiloxane, tetramethyl tetravinyl cyclotetrasiloxane, and vinyl-tri(2-methoxyethoxy) silane.

[0013] Preferably, the concentration of the aqueous ammonia solution is 0.4-0.5wt.%, for example, 0.4wt.%, 0.42wt.%, 0.44wt.%, 0.46wt.%, 0.48wt.%, 0.5wt.%, etc.

[0014] Preferably, the mass ratio of the methylsilane to the vinylsilane is 1:(8-20), for example, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, etc.

[0015] Preferably, the mass ratio of the methylsilane to the aqueous ammonia solution is 1:(100-150), for example, 1:100, 1:105, 1:110, 1:115, 1:120, 1:125, 1:130, 1:135, 1:140, 1:145, 1:150, etc.

[0016] Preferably, the material of the metal plating layer includes any one of silver, copper, nickel and gold, or a combination of at least two of them.

[0017] Preferably, the thickness of the metal coating is 50 to 300 nm, for example, 50 nm, 60 nm, 80 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, 220 nm, 240 nm, 260 nm, 280 nm, 300 nm, etc., preferably 60 to 300 μm.

[0018] Preferably, the method of coating the metal coating is chemical plating.

[0019] In a second aspect, the present invention provides a method for preparing the conductive particles according to the first aspect, the method comprising the following steps:

[0020] (1) preparing organosilicon microspheres, and sequentially subjecting them to sensitization treatment and activation treatment;

[0021] (2) adding the activated organosilicon microspheres obtained in step (1) into a metal chemical plating solution for chemical plating to obtain the conductive particles having a core-shell structure.

[0022] Preferably, the specific process of preparing the organosilicon microspheres comprises the following steps: adding methylsilane and vinylsilane into an aqueous ammonia solution, reacting, and post-treating to obtain the organosilicon microspheres.

[0023] In the present invention, the organosilicon microspheres are prepared by a hydrolysis polymerization method.

[0024] Preferably, the reaction is carried out under stirring conditions.

[0025] Preferably, the stirring includes magnetic stirring, and the rotation speed is 400-600 rpm, for example, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, etc.

[0026] Preferably, the reaction temperature is 40-60°C, for example 40°C, 45°C, 50°C, 55°C, 60°C, etc., and the reaction time is 20-40 minutes, for example 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, etc.

[0027] Preferably, the post-treatment includes centrifugation, washing, drying and calcination.

[0028] Preferably, the drying temperature is 70-90°C, for example 70°C, 75°C, 80°C, 85°C, 90°C, etc., and the drying time is 10-14 hours, for example 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, etc.

[0029] Preferably, the calcination temperature is 360-400°C, such as 360°C, 370°C, 380°C, 390°C, 400°C, etc., and the calcination time is 1-3 hours, such as 1 hour, 2 hours, 3 hours, etc.

[0030] Preferably, the specific process of the sensitization treatment includes the following steps:

[0031] The organic silicon microspheres are added to Sn-containing 2+ Sensitized organosilicon microspheres were obtained after ultrasonication, washing and drying.

[0032] Preferably, the Sn-containing 2+ The sensitizing solution consists of Sn 2+ The solution is mixed with hydrochloric acid solution.

[0033] Preferably, the Sn-containing 2+ The solution includes SnCl2 solution and / or SnSO4 solution.

[0034] Preferably, the Sn-containing 2+ In the sensitizing solution, Sn 2+ The concentration is 2-4g / L, for example, 2g / L, 2.2g / L, 2.4g / L, 2.6g / L, 2.8g / L, 3g / L, 3.2g / L, 3.4g / L, 3.6g / L, 3.8g / L, 4g / L, etc.

[0035] Preferably, the specific process of the activation treatment includes the following steps:

[0036] The sensitized silicone microspheres were added to the Pd 2+ The activated organosilicon microspheres were obtained after ultrasonication, washing and drying.

[0037] Preferably, the Pd-containing 2+ The solution includes any one of (NH4)2PdCl4 solution, PdCl2 solution, and PdSO4 solution, or a combination of at least two of them.

[0038] Preferably, the Pd-containing 2+ In the solution, Pd 2+ The concentration is 0.5-1g / L, for example, 0.5g / L, 0.6g / L, 0.7g / L, 0.8g / L, 0.9g / L, 1g / L, etc.

[0039] Preferably, the specific process of chemical plating includes the following steps:

[0040] The activated organosilicon microspheres obtained in step (1) are added into a metal chemical plating solution, stirred for reaction, centrifuged, washed and dried to obtain the conductive particles having a core-shell structure.

[0041] Preferably, the raw materials for preparing the metal chemical plating solution include metal salt, reducing agent, complexing agent, buffer, stabilizer and deionized water.

[0042] Preferably, the metal salt includes any one of nickel sulfate, silver nitrate, copper sulfate, chloroauric acid, or a combination of at least two thereof.

[0043] Preferably, the reducing agent comprises sodium hypophosphite and / or dimethylamine borane.

[0044] Preferably, the complexing agent includes any one of succinic acid, pyrophosphate, sodium citrate, and ammonium salt, or a combination of at least two thereof.

[0045] Preferably, the buffer comprises sodium acetate.

[0046] Preferably, the stabilizer comprises thallium nitrate and / or ammonium chloride.

[0047] Preferably, in the metal chemical plating solution, based on 1L of deionized water, the amount of the metal salt is 0.1-0.3mol (for example, 0.1mol, 0.12mol, 0.14mol, 0.16mol, 0.18mol, 0.2mol, 0.22mol, 0.24mol, 0.26mol, 0.28mol, 0.3mol, etc.), the amount of the reducing agent is 0.8-3mol (for example, 0.8mol, 0.9mol, 1mol, 1.2mol, 1.4mol, 1.6mol, 1.8mol, 2mol, 2.2mol, 2.4mol, 2.6mol, 2.8mol, 3mol, etc.), and the amount of the complexing agent is 0.2-1mol l (for example 0.2mol, 0.3mol, 0.4mol, 0.5mol, 0.6mol, 0.7mol, 0.8mol, 0.9mol, 1mol, etc.), the amount of the buffer is 0.2-0.4mol (for example 0.2mol, 0.22mol, 0.24mol, 0.26mol, 0.28mol, 0.3mol, 0.32mol, 0.34mol, 0.36mol, 0.38mol, 0.4mol, etc.), and the amount of the stabilizer is 0.2-1mol (for example 0.2mol, 0.3mol, 0.4mol, 0.5mol, 0.6mol, 0.7mol, 0.8mol, 0.9mol, 1mol, etc.).

[0048] Preferably, the stirring reaction temperature is 50-60°C, such as 50°C, 55°C, 60°C, etc., and the stirring reaction time is 10-30 minutes, such as 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, etc.

[0049] The present invention uses the prepared organosilicon microspheres as the core, and has the advantages of uniform and controllable particle size, high temperature resistance, good breakage resistance, etc.; the modulus of the conductive particles can be adjusted by regulating the thickness of the metal coating, and the process is gentle and simple; the conductive particles provided by the present invention have broad application prospects in scenarios with high temperatures and high requirements on particle pressure resistance.

[0050] In a third aspect, the present invention provides a use of the conductive particles as described in the first aspect in an anisotropic conductive adhesive.

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] The conductive particles obtained by using silicone microspheres as the core of the present invention have the advantages of uniform and controllable particle size, high temperature resistance, good crushing resistance, etc.; the modulus of the conductive particles can be adjusted by regulating the thickness of the metal plating layer, and the process is gentle and simple; the conductive particles provided by the present invention have broad application prospects in scenarios with high temperatures and high requirements on particle pressure resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 Thermogravimetric analysis diagrams of the organosilicon microspheres provided in Comparative Example 1, the organosilicon microspheres nickel-plated conductive particles prepared in Example 1, and commercially available polymer gold-plated conductive microspheres (model Sekisui AU-205).

[0054] Figure 2A , Figure 2B The scanning electron microscope image and particle size distribution diagram of the organosilicon microspheres provided in Comparative Example 1 are shown respectively.

[0055] Figure 3 (a) Figure 3 (b) are respectively a high-magnification scanning electron microscope image of the nickel-plated conductive particles of the silicone microspheres prepared in Example 1 and a characterization image of the thickness of the metal coating.

[0056] Figure 4A , Figure 4B They are respectively a scanning electron microscope image and a particle size distribution diagram of the nickel-plated conductive particles of the silicone microspheres prepared in Example 2.

[0057] Figure 5 (a) Figure 5 (b) are respectively a high-magnification scanning electron microscope image of the nickel-plated conductive particles of the silicone microspheres prepared in Example 2 and a characterization image of the thickness of the metal coating.

[0058] Figure 6 (a) Figure 6(b) are respectively a high-magnification scanning electron microscope image of the nickel-plated conductive particles of the silicone microspheres prepared in Example 3 and a characterization image of the thickness of the metal coating.

[0059] Figure 7 The pressure-displacement curve of the nanoindentation test of a single organosilicon microsphere nickel-plated conductive particle prepared in Example 1, Example 2 and Example 3. DETAILED DESCRIPTION

[0060] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0061] Example 1

[0062] In this embodiment, a conductive particle is provided, and a preparation method thereof comprises the following steps:

[0063] (1) Preparation of silicone microspheres

[0064] 300 g of 0.42 wt.% ammonia solution was slowly added into a 500 mL four-necked flask, and then 2.5 g of methyltrimethoxysilane (MTMS) and 25 g of vinyltrimethoxysilane (VTMO) were slowly added into the four-necked flask, and stirred to react. The reaction conditions were magnetic stirring, a rotation speed of 500 rpm, a reaction temperature of 50°C, and a reaction time of 30 minutes. After the reaction, the solution was taken out, centrifuged, washed, dried at 80°C for 12 hours, and calcined at 380°C for 2 hours to obtain silicone microspheres.

[0065] (2) Silicone microsphere sensitization

[0066] Weigh 0.09g of hydrochloric acid solution (concentration of 36.0-38.0%) and 0.2g of SnCl2 and add them into 50g of deionized water to prepare a SnCl2 sensitized solution; disperse the silicone microspheres in deionized water, ultrasonically disperse for 20 minutes, and then centrifuge and wash for use; add the dispersed silicone microspheres to the SnCl2 sensitized solution, ultrasonically disperse for 30 minutes, then centrifuge, and then wash with deionized water and dry to obtain sensitized silicone microspheres.

[0067] (3) Activation of silicone microspheres

[0068] The sensitized organosilicon microspheres were dispersed in a 1 g / L PdSO4 solution and washed by centrifugation after ultrasonic treatment for 30 minutes and dried to obtain activated organosilicon microspheres.

[0069] (4) Preparation of chemical plating solution

[0070] The chemical plating solution consists of nickel sulfate (0.2 mol / L), dimethylamine borane (1 mol / L), sodium citrate (0.5 mol / L), sodium acetate (0.3 mol / L) and ammonium chloride (0.5 mol / L), and the solvent is deionized water.

[0071] (5) Chemical plating

[0072] The activated organosilicon microspheres were dispersed in a chemical plating solution, mechanically stirred in a 55° C. water bath, reacted for 20 minutes, centrifuged, washed, and dried to obtain organosilicon microsphere nickel-plated conductive particles.

[0073] Comparative Example 1

[0074] In this comparative example, a silicone microsphere is provided. The preparation method is the same as step (1) in Example 1. The diameter of the prepared silicone microsphere is about 3 μm. The silicone microspheres provided in Comparative Example 1, the nickel-plated conductive particles of the silicone microspheres prepared in Example 1, and the commercially available polymer gold-plated conductive microspheres (model Sekisui AU-205) are tested by a thermogravimetric analyzer. The results are as follows: Figure 1 As shown, it can be seen that the organosilicon microsphere nickel-plated conductive particles provided in Example 1 have higher thermal stability.

[0075] The organosilicon microspheres provided in Comparative Example 1 were characterized by scanning electron microscopy, and the particle size distribution was statistically analyzed. The scanning electron microscope image and the particle size distribution graph are shown as follows: Figure 2A and Figure 2B As shown, it can be seen that the surface sphericity of the silicone microspheres is high, the particle size is uniform, the dispersion is good, and the average particle size is about 3.03 μm.

[0076] The high-magnification scanning electron microscope image of the nickel-plated conductive particles of the organosilicon microspheres provided in Example 1 and the characterization image of the thickness of the metal coating are shown as follows: Figure 3 (a) Figure 3 (b) as shown.

[0077] Example 2

[0078] The only difference between this embodiment and embodiment 1 is that the amount of the reducing agent (dimethylamine borane) used in step (4) is 2 mol / L.

[0079] The nickel-plated conductive particles of the organosilicon microspheres prepared in this embodiment were characterized by scanning electron microscopy, and the particle size distribution was statistically analyzed. The scanning electron microscope image and the particle size distribution graph are shown in FIG. Figure 4A and Figure 4B As shown, it can be seen that the uniformity and dispersion of the nickel-plated conductive particles of the silicone microspheres are good, and the average particle size is about 3.29 μm.

[0080] The high-magnification scanning electron microscope image of the nickel-plated conductive particles of the organosilicon microspheres provided in this embodiment and the characterization image of the thickness of the metal coating are shown in Figures 1 and 2. Figure 5 (a) Figure 5 (b) as shown.

[0081] Example 3

[0082] The only difference between this embodiment and embodiment 1 is that the amount of the reducing agent (dimethylamine borane) used in step (4) is 3 mol / L.

[0083] The high-magnification scanning electron microscope image of the nickel-plated conductive particles of the organosilicon microspheres provided in this embodiment and the characterization image of the thickness of the metal coating are shown in Figures 1 and 2. Figure 6 (a) Figure 6 (b) as shown.

[0084] The single organosilicon microsphere nickel-plated conductive particles provided in Examples 1-3 were compressed respectively on the smooth indenter end face of a cylinder (diameter 20 μm, made of diamond) at a compression speed of 2 mN / s and a maximum load of 11000 μN, and the modulus of the conductive particles was tested using a pointed probe. The test results are shown in FIG. Figure 7 As shown, it can be seen that the modulus of the conductive particles can be adjusted by regulating the thickness of the metal coating.

[0085] Example 4

[0086] The difference between this embodiment and embodiment 1 is that the type of methyl silane in step (1) is methyltriethoxysilane, and the type of vinyl silane is vinyltriethoxysilane.

[0087] Example 5

[0088] The difference between this embodiment and embodiment 1 is that the amount of vinyltrimethoxysilane used in step (1) is 50 g.

[0089] Comparative Example 2

[0090] In this comparative example, a conductive particle is provided, and the preparation method comprises the following steps:

[0091] (1) Wash 3 μm polystyrene microspheres for 30 min;

[0092] (2) immersing the cleaned polystyrene microspheres in a 3 g / L PdSO4 aqueous solution for sensitization, and washing the excess ions on the surface with deionized water;

[0093] (3) The cleaned microspheres were placed in a nickel sulfate / sodium citrate aqueous solution (80 g nickel sulfate: 40 g sodium citrate: 1 L deionized water), 100 g dimethylamine borane (DMAB) was added to the mixed solution to achieve nickel plating on the surface of the microspheres, and finally the conductive microspheres were cleaned and collected.

[0094] The conductive particles provided in Examples 1 to 5 of the present invention and Comparative Example 2, and the organosilicon microspheres provided in Comparative Example 1 were tested for performance, and the testing method was as follows:

[0095] (1) Modulus: A nanoindenter was used to compress a single conductive particle or silicone microsphere on the smooth indenter end face of a cylinder (diameter 20 μm, made of diamond) at a compression speed of 2 mN / s and a maximum load of 11000 μN. The modulus of the conductive particle was tested using a pointed probe.

[0096] (2) Crushing force: The crushing force of conductive particles was measured using a nanoindenter on the smooth indenter end surface of a cylinder (diameter 20 μm, made of diamond) at a compression rate of 2 mN / s.

[0097] (3) Resistivity: A powder resistance meter is used to characterize the powder resistivity of the conductive particles. The test conditions are: the mass of the solid powder sample is about 0.2 g, the pressure range is 10 MPa to 120 MPa, and the resistivity corresponding to the pressure of 120 MPa is taken.

[0098] The performance test results are shown in Table 1.

[0099] Table 1

[0100]

[0101] It can be seen from Table 1 that the conductive particles provided in the embodiments of the present invention have good crushing resistance (the crushing force is greater than 10000 μN), and the hardness of the conductive particles is adjustable.

[0102] Comparative Example 1 provides a kind of organic silicon microsphere, which has no conductivity; Comparative Example 2 provides conductive particles with poor crushing resistance and low modulus.

[0103] The residual rate of the samples at different thermal cracking temperatures was tested on the conductive particles provided in Examples 1-5 and Comparative Example 2, and the silicone microspheres provided in Comparative Example 1 using a thermogravimetric analyzer, and the temperatures corresponding to 3% and 5% weight loss rates were tested, respectively. The test results are shown in Tables 2 and 3, respectively.

[0104] Table 2 Residual rate of samples at different pyrolysis temperatures

[0105]

[0106]

[0107] Table 3 The corresponding temperatures of samples at 3% and 5% weight loss

[0108] 3% weight loss temperature (℃) 5% weight loss temperature (℃) Example 1 469 659 Example 2 583 >800 Example 3 590 >800 Example 4 443 650 Example 5 472 674 Comparative Example 1 463 547 Comparative Example 2 407 430 AU-205 403 432

[0109] It can be seen from Table 2 and Table 3 that the conductive particles provided by the embodiments of the present invention have good high temperature resistance.

[0110] The high temperature resistance of the organosilicon microspheres provided in Comparative Example 1, the conductive particles provided in Comparative Example 2, and the commercially available AU-205 are all significantly poor.

[0111] The applicant declares that the present invention illustrates the conductive particles and the preparation method and application thereof through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A conductive particle, characterized in that: The conductive particles have a core-shell structure, the core layer of the conductive particles is organic silicon microspheres, and the shell layer is a metal coating.

2. The conductive particle according to claim 1, characterized in that The particle size of the organosilicon microspheres is 1 to 200 μm; Preferably, the raw materials for preparing the organosilicon microspheres include: methylsilane, vinylsilane and ammonia solution; Preferably, the methylsilane includes any one of methyltrimethoxysilane, methyltriethoxysilane, polydimethylsiloxane, mercaptopropyltrimethoxysilane, hexamethyldisiloxane, cyclomethylsiloxane, polymethylphenylsiloxane, or a combination of at least two thereof; Preferably, the vinyl silane is selected from any one or a combination of at least two of vinyl trimethoxy silane, vinyl triethoxy silane, tetramethyl divinyl disiloxane, tetramethyl tetravinyl cyclotetrasiloxane, and vinyl tris (2-methoxyethoxy) silane; Preferably, the concentration of the aqueous ammonia solution is 0.4 to 0.5 wt.%; Preferably, the mass ratio of methylsilane to vinylsilane is 1:(8-20); Preferably, the mass ratio of the methylsilane to the aqueous ammonia solution is 1:(100-150).

3. The conductive particle according to claim 1 or 2, characterized in that: The material of the metal plating layer includes any one of silver, copper, nickel, and gold, or a combination of at least two thereof; Preferably, the thickness of the metal coating is 50 to 300 nm; Preferably, the method of coating the metal coating is chemical plating.

4. A method for preparing conductive particles according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) preparing organosilicon microspheres, and sequentially subjecting them to sensitization treatment and activation treatment; (2) adding the activated organosilicon microspheres obtained in step (1) into a metal chemical plating solution for chemical plating to obtain the conductive particles having a core-shell structure.

5. The preparation method according to claim 4, characterized in that: The specific process of preparing the organosilicon microspheres comprises the following steps: adding methylsilane and vinylsilane into an ammonia solution, reacting, and post-treating to obtain the organosilicon microspheres; Preferably, the reaction is carried out under stirring conditions; Preferably, the stirring comprises magnetic stirring at a speed of 400 to 600 rpm; Preferably, the reaction temperature is 40 to 60° C., and the reaction time is 20 to 40 minutes; Preferably, the post-treatment includes centrifugation, washing, drying and calcination; Preferably, the drying temperature is 70 to 90° C. and the drying time is 10 to 14 hours; Preferably, the calcination temperature is 360-400° C., and the calcination time is 1-3 hours.

6. The preparation method according to claim 4 or 5, characterized in that: The specific process of the sensitization treatment includes the following steps: The organic silicon microspheres are added to Sn-containing 2+ Sensitized organic silicon microspheres are obtained after ultrasonication, washing and drying in a sensitizing solution; Preferably, the Sn-containing 2+ In the sensitizing solution, Sn 2+ The concentration is 2-4 g / L.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The specific process of the activation treatment comprises the following steps: The sensitized silicone microspheres were added to the Pd 2+ In a solution of , activated organosilicon microspheres are obtained after ultrasonication, washing and drying; Preferably, the Pd-containing 2+ The solution includes any one of (NH4)2PdCl4 solution, PdCl2 solution, and PdSO4 solution, or a combination of at least two thereof; Preferably, the Pd-containing 2+ In the solution, Pd 2+ The concentration is 0.5~1g / L.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The specific process of the chemical plating comprises the following steps: The activated organosilicon microspheres obtained in step (1) are added into a metal chemical plating solution, stirred for reaction, centrifuged, washed and dried to obtain the conductive particles having a core-shell structure.

9. The preparation method according to any one of claims 4 to 8, characterized in that: The raw materials for preparing the metal chemical plating solution include metal salt, reducing agent, complexing agent, buffer, stabilizer and deionized water; Preferably, the metal salt includes any one of nickel sulfate, silver nitrate, copper sulfate, chloroauric acid, or a combination of at least two thereof; Preferably, the reducing agent comprises sodium hypophosphite and / or dimethylamine borane; Preferably, the complexing agent includes any one of succinic acid, pyrophosphate, sodium citrate, and ammonium salt, or a combination of at least two thereof; Preferably, the buffer comprises sodium acetate; Preferably, the stabilizer comprises thallium nitrate and / or ammonium chloride; Preferably, in the metal chemical plating solution, based on 1L of deionized water, the amount of the metal salt is 0.1-0.3 mol, the amount of the reducing agent is 0.8-3 mol, the amount of the complexing agent is 0.2-1 mol, the amount of the buffer is 0.2-0.4 mol, and the amount of the stabilizer is 0.2-1 mol; Preferably, the stirring reaction temperature is 50 to 60° C., and the stirring reaction time is 10 to 30 minutes.

10. Use of the conductive particles according to any one of claims 1 to 3 in anisotropic conductive adhesive.